2014
DOI: 10.1200/jco.2013.53.6995
|View full text |Cite
|
Sign up to set email alerts
|

Second-Line Oxaliplatin, Folinic Acid, and Fluorouracil Versus Folinic Acid and Fluorouracil Alone for Gemcitabine-Refractory Pancreatic Cancer: Outcomes From the CONKO-003 Trial

Abstract: Second-line OFF significantly extended the duration of overall survival when compared with FF alone in patients with advanced gemcitabine-refractory pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
304
1
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 425 publications
(335 citation statements)
references
References 24 publications
16
304
1
14
Order By: Relevance
“…In the OFF arm, the median OS and TTP were significantly extended in comparison to the 5-FU arm. The toxicities were similar between the two groups except for neurotoxicity, in 38.2% of OFF group patients [72] . However, oxaliplatinbased regimens for second-line chemotherapy have not given only positive outcomes.…”
Section: Current Knowledgementioning
confidence: 73%
“…In the OFF arm, the median OS and TTP were significantly extended in comparison to the 5-FU arm. The toxicities were similar between the two groups except for neurotoxicity, in 38.2% of OFF group patients [72] . However, oxaliplatinbased regimens for second-line chemotherapy have not given only positive outcomes.…”
Section: Current Knowledgementioning
confidence: 73%
“…This approach was informed in large part by results from one of the largest randomized studies (a German trial called CONKO-003) in this disease setting demonstrating a survival advantage of OFF (oxaliplatin, folinic acid, and fluorouracil) compared to FF alone (median OS: 5.9 vs 3.3 months, HR =0.66; log-rank P=0.010). 18 Conversely, a later trial conducted in Canada called PANCREOX showed almost the precise opposite results in a similar patient population, with patients treated with FOLFOX (chemotherapy regimen of folinic acid, 5-FU, and oxaliplatin) faring no better -and possibly worse -than those receiving 5-FU/LV alone. 19 In addition to nal-IRI, several other novel agents have shown promising results in the second-line (and beyond) setting for metastatic pancreatic cancer and are moving ahead in clinical development.…”
Section: Nanoliposomal Irinotecan In Pancreatic Cancermentioning
confidence: 99%
“…Second line OFF chemotherapy regimen was significantly improved OS and PFS in patients with metastatic pancreas cancer who were progressed during first-line gemcitabine monotherapy. 35 After the positive results of these trials, the NCCN Guidelines recommends fluropyrimidine plus oxaliplatin as a second-line treatment option. Although these trials used the OFF regimen most of the clinicians used the FOLFOX (oxaliplatin 85 mg/m 2 on day 1, 5-FU 400 mg/m 2 IV on day 1 followed by 2400 mg/m 2 continuous infusion over 46 hours, and leucovorin 400 mg/m 2 IV on day 1 repeated every 14 days) regimen as a second line therapy.…”
Section: Off or Folfoxmentioning
confidence: 99%